EFFECTIVENESS OF PURSULA (Portulaca oleracea) FATTY ACID EXTRACTS IN REDUCE THE TRIGLYCERIDES OF OBESITY RATS - Atok Miftachul Hudha; Larasati Dwi Cahyaning Putri; Fendy Hardian Permana (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Hyperlipidemia is a condition of high levels of lipids in the blood. Hyperlipidemia is a major factor causing non-communicable diseases such as DMT2 and stroke. Purslane is a plant that contains PUFA which is hypolipidemic. The purpose of this study was to test the effectiveness of giving purslane plant fatty acid extracts in reducing triglyceride levels in obese rats induced by a high-fat and high-calorie diet. There were five treatments in this study, namely P1 negative control (no treatment), P2 positive control (by administering gemfibrozil), P3 (100 mg/kg BW of purslane fatty acid extract), P4 (200 mg/kg BW of purslane fatty acid extract), P5 (300 mg/kg BW of purslane fatty acid extract). The test animals used were male rats strain Ratus norvegitus, male, initial body weight ± 200 grams with final body weight ≥ 10% of initial weight. This research is True-Eksperimental Research using a Control Group Pretest-Posttest Design with the RAL experimental design. The data obtained were analyzed statistically using tests Quade's Rank Analysis of Covariance. The results showed that the purslane plant fatty acid extract could reduce triglyceride levels. In this study, a dose of 300 mg/kg BW was the best dose for reducing triglyceride levels in obese rats.